Sampling design modifications to a fishery-independent monitoring survey balance the maintenance of long-term data with emerging management needs and funding limitations - Schrandt, Meagan N.; MacDonald, Timothy C.; Winner, Brent L.; Blewett, David A.; Paperno, Richard; Onorato, Gregory V.; Gandy, David A.; Switzer, Theodore S. (Frontiers in Marine Science, 2024)
Development of Florida’s marine Fisheries-Independent Monitoring (FIM) program began in 1985, and it initiated long-term monitoring in Tampa Bay in 1989 with the purpose of providing timely fishery-independent data and analyses to fishery managers for the conservation and protection of the species that support Florida’s fisheries. Over time, the program expanded sampling in other Florida estuaries. Data from this monitoring program are integral to the assessment and management of numerous state and federally managed fishes, so long-term consistency is of paramount importance, but sampling design modifications have been necessary over time. This review presents three case studies in which the estuarine component of the FIM program was changed to address emerging data needs in management of Florida’s fishery resources, while maintaining standardization and consistency with long-term surveys statewide. In the first case study, survey changes increased the amount of data on juvenile common snook, Centropomus undecimalis, on the Gulf of Mexico and Atlantic coasts and improved indices of abundance, survival estimates, and age-length keys for state management purposes. In the second case study, the FIM program improved estimates of abundance of juvenile reef fishes by initiating a complementary survey that expanded FIM sampling to new regions of the Florida Gulf coast and targeted a unique habitat (polyhaline seagrass beds along estuarine shoal habitats) not previously sampled in the standard long-term survey. In the third case study, the FIM program addressed a data limitation for regional management of spotted seatrout, Cynoscion nebulosus, by initiating seasonal sampling in western Florida. In each case study, the standard long-term survey design was modified to include sampling of new and unique areas and habitats, providing valuable data on estuarine fish assemblages that support analyses at the broader, ecosystem level. Survey amendments were designed to maintain standardization and consistency, all with limited additional funding. The success of these survey modifications was the result of several key factors: mission-focused programmatic goals, geographically dispersed laboratories, standardized protocols, ongoing critical analysis of the data, grant award success, and high-level data management. Although each case study originated with a survey expansion, all were followed by survey reductions or streamlining, so expansion and reduction scenarios are presented in this review. Regardless of these modifications, the mission of the FIM program remains the same: to provide timely data and analysis for the use of fishery managers, including state and federal partners.